Single-Cell Biophysical Study Reveals Deformability and Internal Ordering Relationship in T Cells - Garcia-Herrera, C; Navarrete-Rosales, A (Royal Society of Chemistry, 2020)
Deformability and internal ordering are key features related to cell function, particularly critical for cells that routinely undergo large deformations, like T cells during extravasation and migration. In the measurement of cell deformability, a considerable variability is typically obtained, masking the identification of possible interrelationships between deformability, internal ordering and cell function. We report the development of a single-cell methodology that combines measurements of living-cell deformability, using micropipette aspiration, and three-dimensional confocal analysis of the nucleus and cytoskeleton. We show that this single-cell approach can serve as a powerful tool to identify appropriate parameters that characterize deformability within a population of cells, not readably discernable in population-averaged data. By applying this single-cell methodology to mouse CD4+ T cells, our results demonstrate that the relative size of the nucleus, better than other geometrical or cytoskeletal features, effectively determines the overall deformability of the cells within the population. This journal is © 2020 The Royal Society of Chemistry.